Integração dos ODS ao atendimento da Agenda 2030: um estudo no Instituto Federal Sul Rio-grandense de Passo Fundo/RS - Pinzon, Jaqueline (2023)
Higher Education Institutions (HEIs) play a fundamental role in transforming societies towards a more sustainable future, especially through the dissemination of knowledge, research, education and extension, in driving sustainable development. Thus, the objective of this Dissertation is to explore the contribution of IFSul-RS to the implementation of the 2030 Agenda based on its actions, engagement and challenges. This is an applied research, classified as qualitative, of an exploratory nature, using some assumptions of participatory action research. Furthermore, it constitutes a case study, in relation to its technical procedures, with documentary research and survey research. The information obtained through the questionnaire, by Bardin's content analysis (2016). The research was carried out in the city of Passo Fundo/RS, between 2022 -2023, at IFSul, and was composed of eleven students, identified as Group 1 (G1). The results of this research regarding the characterization of the sample demonstrated that the average age of G1 is 22 years, 80% male and 20% female, 100% enrolled in the Computer Science course. After analyzing the speeches expressed, it was found that the analysis categories CP, CR and CA in the students' perception indicate that knowledge about Sustainable Development and the information they have determine their involvement with sustainability. The sample of Group 2 (G2) was composed of five Managers and seven Teachers, with an average age of 42 years, 70% male and 30% female, 34% with a degree in Computer Science, 25% in Full Degree in Mathematics, 17% in Civil Engineering, 8% in Mechanical Engineering, 8% in Electrical Engineering and 8% in Law, in relation to qualifications 67% have a Master's degree and 33% a Doctorate. After analyzing the statements expressed, it was found that regarding the CP, CR and CA analysis categories in the perception of G2, the vision, actions and attitudes regarding Sustainable Development, as well as the information they have, determine their knowledge and involvement with sustainability. Finally, it is concluded that the contribution of IFSul-RS to the implementation of the 2030 Agenda based on its actions has gradually expanded through a set of instruments to achieve the SDGs. Regarding the objective aimed at proposing sustainability actions, it was achieved through the indication of thirteen actions that will enhance the 2030 Agenda at the IFSul Passo Fundo campus, which include governance actions, engagement of the academic community, communication and teaching, research and extension activities focused on sustainability.